Dissonâncias em busca da harmonia melódica: experiências históricas, desafios, lutas e associativismo da classe musical (SP, 1913-1949) - Freire, Breno Ampáro Alvares (2023)
This thesis aims to problematize, analyze, and question the working conditions and organization of orchestra musicians in São Paulo from 1913 to 1949, tracking how the category created, dynamized and made itself based on struggle strategies. Furthermore, it aims to reconstitute and scrutinize the musical daily life of these workers, as well as to note networks, branches and associative circuits through which those artists managed to articulate themselves. The cut takes as time frames in 1913, the year of the foundation of Centro Musical de São Paulo and when there is news of a “strike” called by the category, and in 1949, when Law No. 3.829 was enacted, decreeing the creation of Orquestra Sinfônica Municipal de São Paulo. The documentary base is made up of news from the press, petitions and official opinions, statutes and program notes. Focusing on the first half of the 20th century, the investigation seeks to problematize the contradictions verified in the musical daily life of the city. Ways of seeing, hearing, and experiencing art underwent radical metamorphoses in the period, driven by the advent of cinema, radio and the incipient music industry. In addition to the technological challenges, there was also the absence of a work circuit focused on concert music – characterized by seasonal seasons, work in symphony orchestras was divided between the theaters’ stages, concert halls and cafes, pits and small movie theaters. The remuneration was uncertain, living on the provision of musical services. The association experiences that emerged were the way to unite, protect and organize a category that fought for better living conditions. The mutualist character of the musical entities was mixed with a claiming wave, which would be perceived more incisively from the 1930s onwards, with the rise of Getulio Vargas to the government and the establishment of a centralizing federal agenda with regard to the protection, control and surveillance of the working class. From then on, the emergence of musicians’ unions was inserted in a context of strategic adherence to federal deliberations, as well as internal disputes for recognition and autonomy in the organization of concert music workers